A new archaeocete and other marine mammals (Cetacea and Sirenia) from lower middle Eocene phosphate deposits of Togo. (January 2014) - Gingerich, Philip D.; Cappetta, Henri
Abstract : Lutetian lower middle Eocene phosphate deposits of Kpogamé-Hahotoé in Togo yield new information about whales and sea cows in West Africa. Most specimens are individual teeth and bones, collected as isolated elements, but some appear to have been associated. Most are conservatively interpreted to represent a new 300–400 kg protocetid archaeocete, Togocetus traversei . This genus and species is distinctly primitive for a protocetid in retaining a relatively small mandibular canal in the dentary and retaining a salient metaconid on the lower first molar (M1 ), but it is derived relative to earlier archaeocetes in having large, dense, osteosclerotic tympanic bullae. Mandibular canal size and large dense bullae are not as tightly linked in terms of function in hearing as previously thought. Postcranially Togocetus traversei had many characteristics found in other semiaquatic protocetids: a relatively long neck, mobile shoulder, digitigrade manus, large pelvis, well-developed hind limbs, and feet specialized for swimming. Loss of a fovea on the head of the femur indicates loss of the teres ligament stabilizing the hip, which is a derived specialization consistent with life in water. Protocetid specimens distinctly smaller and larger than those of Togocetus traversei indicate the presence of at least three protocetids at Kpogamé. Sirenian vertebral and rib pieces indicate the presence of a protosirenid and a dugongid. Finally, a vertebral centrum and piece of humerus appear to represent a large land mammal. A diverse fauna of archaic whales and early sirenians inhabited the western margin of Africa and the eastern Atlantic Ocean as early as 46–44 million years before present, showing that both cetaceans and sirenians were widely distributed geographically by this time.